Vegetables consumers' profile in the context of digitalization: Evidence from Romania - Lucian Tanasă; Simona-Roxana Ulman; Cristina Cautisanu; Ioan Sebastian Brumă; Daniel Juravle (Amfiteatru Economic Journal, 2022)
The objectives of the European Green Deal are closely related to digitalization as a key factor in achieving them. Accordingly, this study aims at analysing the differences among the profiles of consumers from Romania regarding the method of payment used in online purchasing of fresh vegetables from local producers. Using Multiple Correspondence Analysis and Logistic Regression, main results showed similarity in consumers' profiles using debit card and bank transfer, where individuals with ages between 19-49, with an income in the household equal to at least 6,000 RON (1,213 EUR), having at least a Master's Degree and a high frequency of buying products online, are mostly included while, in the case of cash payment, the following characteristics were observed: age between 50-64, income between 3,000-4,499 RON (606-909 EUR), mainly Bachelor's Degree, and a low frequency of buying products online. Our results revealed that local vegetable producers should be prepared to adapt themselves to digitalization. People seem to be open to it and, for responding to such digital needs, the farmers must get out their comfort zone and become aware that this adaptation becomes a mandatory requirement on the actual market.
Keywords: D01; D12; O14; Q13; 330; digitalization; local vegetable producers; consumers' profile; on-line purchase; method of payment; short supply chains; Romania